2019
DOI: 10.1038/s41401-019-0318-5
|View full text |Cite
|
Sign up to set email alerts
|

Xanthatin induces glioma cell apoptosis and inhibits tumor growth via activating endoplasmic reticulum stress-dependent CHOP pathway

Abstract: Xanthatin is a natural sesquiterpene lactone purified from Xanthium strumarium L. , which has shown prominent antitumor activity against a variety of cancer cells. In the current study, we investigated the effect of xanthatin on the growth of glioma cells in vitro and in vivo, and elucidated the underlying mechanisms. In both rat glioma C6 and human glioma U251 cell lines, xanthatin (1–15 μM) dose-dependently inhibited cell viability without apparent effect on the cell cycle. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…CHOP is an important transcription factor involved in regulating apoptosis and drug sensitivity [168][169][170]. Studies have shown that the levels of CHOP mRNA and its protein level were significantly lower in lung cancer tissues compared with noncancerous tissues.…”
Section: Therapeutic Strategies Based On Ncrnas and The Upr In Cancermentioning
confidence: 99%
“…CHOP is an important transcription factor involved in regulating apoptosis and drug sensitivity [168][169][170]. Studies have shown that the levels of CHOP mRNA and its protein level were significantly lower in lung cancer tissues compared with noncancerous tissues.…”
Section: Therapeutic Strategies Based On Ncrnas and The Upr In Cancermentioning
confidence: 99%
“…For the detection of ER stress, the ER stress inhibitor 4-phenylbutyric acid (4-PBA; Sigma-Aldrich; Merck KGaA) at a concentration of 7 mM was used to pretreat AGS cells for 4 h at 37˚C, according to a previous study (9), to determine the role of SchA in ER stress.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, after treatment with the test compounds for 18 h, A549 cells were collected and lysed with ice-cold RIPA lysis buffer containing proteinase inhibitors. The expression of TrxR proteins after treatment with the test compounds was analyzed by Western blot as previously described [ 30 ].…”
Section: Methodsmentioning
confidence: 99%